Wenjing Guo, Internet à Canton (Chine) – Dynamiques sociales et politiques - Wenjing Guo (Revue de la Régulation)
Internet and its dissemination in China have profoundly changed the way of communication, expression and mobilization of the Chinese people. The Chinese internet users as well as their government have quickly mastered Internet and new technologies. The former seek more freedom in an authoritarian regime, while the latter endeavors to contain these new dynamics both online and offline, in order to avoid political excesses and so to retain the power. This anthropological research focuses on this permanent confrontation from the formation process and evolution of active social groups on the Internet, who exist thanks to and because of the Internet. The fieldwork centered on three groups around specific issues (homosexuality, environmental protection, cultural heritage protection) in the city of Guangzhou. Using the new paradigm of governance, the Chinese government attempts to control these dynamics through a scheduled participation in the management of social problems for its own interest. Taken between the economic openness and political closure, the networking of the social actors leaves them a compressed but real space and a limited autonomy in spite of all the established controls.